Estudio del enfriamiento de Billets de aluminio de aleación 6063 en el proceso de homogenizado y su influencia en la productividad en el área de extrucsión en la Empresa CEDAL S.A. - Vargas Cabezas, Jackeline Estefanía (2018)
The present project is based on the evaluation of the homogenized process in its third stage, which is the cooling of 6063 alloy aluminum billets, establishing the appropriate method of the cycle to improve the productivity in the extrusion area of the CEDAL S.A company – Latacunga The current homogenization process used was evaluated, of 6063 alloy aluminum billets that have a length of 5.79 m and 0.18 m in diameter, especially the third stage pertaining to the cooling of billets since the company does not It presents a control system that allows to identify the time spent. The third stage of the current process was modified; Through the use of cooling methods, by sprinkling water and cooling to the environment, the temperatures obtained were recorded through the use of seven K-type thermocouple cables distributed over the entire length of the billet, from which different characterizations were obtained in the material, which was subjected to a laboratory analysis to know its grain size and microstructure, allowing to compare the characterization of the material submitted to the different cooling cycles, which was provided to the process. In addition, the production batches studied were monitored, in the extrusion area, and the behavior of the 6063 alloy material in the area was analyzed, recording extrusion speed variables of aluminum profiles, the pressure with which the press, the identification of defects in profiles, the productivity and quality of the material in the area, according to the types of cooling provided to the billets in the homogenization process. The study allowed to identify the adequate method for the cooling stage in the homogenized process and to increase the productivity in the extrusion area while preserving the quality in extruded profiles.